SYSTEM FOR IMPROVING THE EFFECTIVENESS OF ENGLISH LANGUAGE TEACHING IN HIGHER EDUCATION INSTITUTIONS BASED ON A COMPETENCY-BASED APPROACH - Kabulova Zulfiya Xojabayevna (Modern American Journals, 2025)
Within the framework of this scientific research, the current state of the development of oral and written English language skills in the higher education system has been analyzed. The study highlights both globally applied methods and authorial techniques for enhancing oral and writing skills in English.
Keywords: Collaborative, language levels, oral speech, written speech, skill, competence, association, communicative competence, professional competence.